2019
DOI: 10.1111/ecca.12302
|View full text |Cite
|
Sign up to set email alerts
|

School Grants and Education Quality: Experimental Evidence from Senegal

Abstract: The effect of increasing school resources on educational outcomes is a central issue in the debate on improving school quality. In this paper we use a randomized experiment to analyse the impact of a school grants programme in Senegal, which allowed schools to apply for funding for pedagogic improvements of their choice. We find positive effects on test scores at lower grades that persist for at least two years. These effects are concentrated among schools that focused funds on human resources improvements rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Second, while the literature on school grants (Das et al, 2013;Blimpo et al, 2015;Beasley and Huillery, 2017;Carneiro et al, 2020) shows that decentralizing resources and the authority over their use may be a more efficient way to target resources by leveraging better information of local decision-makers, our results show that efficiency gains can be obtained by leveraging mostly existing resources. This result speaks to the growing evidence pointing to the importance of school management in improving learning outcomes through better resource allocation (Abdulkadiroğlu et al, 2011;Dobbie and Fryer, 2013;Rockoff et al, 2012;Taylor and Tyler, 2012;Fryer, 2014;Fryer, 2017).…”
Section: Introductionmentioning
confidence: 69%
“…Second, while the literature on school grants (Das et al, 2013;Blimpo et al, 2015;Beasley and Huillery, 2017;Carneiro et al, 2020) shows that decentralizing resources and the authority over their use may be a more efficient way to target resources by leveraging better information of local decision-makers, our results show that efficiency gains can be obtained by leveraging mostly existing resources. This result speaks to the growing evidence pointing to the importance of school management in improving learning outcomes through better resource allocation (Abdulkadiroğlu et al, 2011;Dobbie and Fryer, 2013;Rockoff et al, 2012;Taylor and Tyler, 2012;Fryer, 2014;Fryer, 2017).…”
Section: Introductionmentioning
confidence: 69%
“…Participating in the Erasmus + program and its external dimension by supporting the modernization of higher education is in first steps in increasing the quality of higher education. Carneiro et al (2020) found that impact of grants in education in quality and learning has its impact when its combined with government and heads of schools involvement 'especially on girls and students with high ability levels at baseline, at a cost effectiveness rate commensurate with other interventions that aim to improve education outcomes in low-income countries'. In Kosovo population is the youngest in Europe and unemployment levels are approximately as high as 35 percent.…”
Section: Discussionmentioning
confidence: 99%
“…According to (Becker, 1964), human capital is directly needed in the production process, more explicitly human capital increases the productivity of employees in all tasks, but normally differently in different tasks and different organizations, e. which although generalized makes sense since the level of knowledge and ability of employees is directly related to the function of productivity. When it comes to grants in education according to Carneiro et al (2020) sometimes government and authorities does not know the needs of the schools and universities and therefore we do not see improvement in their general scores .whilst when comes to the labor market to select and retain a satisfying employee there are some issues that needs to be developed as training and development and interaction of organizations strategy with human resources development , in order to reach competitive advantage in the field that they are working Holland et al (2007). Sun, M., Penner, E. K., & Loeb, S. (2017).…”
Section: Methodsmentioning
confidence: 99%
“…According to (Becker, 1964), human capital is directly needed in the production process, more explicitly human capital increases the productivity of employees in all tasks, but normally differently in different tasks and different organizations, e. which although generalized makes sense since the level of knowledge and ability of employees is directly related to the function of productivity. When it comes to grants in education according to Carneiro et al (2020) sometimes government and authorities does not know the needs of the schools and universities and therefore we do not see improvement in their general scores .whilst when comes to the labor market to select and retain a satisfying employee there are some issues that needs to be developed as training and development and interaction of organizations strategy with human resources development , in order to reach competitive advantage in the field that they are working Holland et al (2007). Sun, M., Penner, E. K., & Loeb, S. ( 2017).…”
Section: Methodsmentioning
confidence: 99%